Θεραπείες ασθενειών με ζωϊκής προελεύσεως ύλες στα βυζαντινά ιατρικά κείμενα. Συμβολή στην μελέτη των αντιλήψεων για τις ασθένειες και τις θεραπείες τους στο Βυζάντιο - ΧΡΟΝΗ, Μαρία (Byzantina Symmeikta, 2011)
TREATMENT OF DISEASES WITH ANIMAL ORIGIN MATERIALS IN BYZANTINE MEDICAL TEXTS: CONTRIBUTION TO THE STUDY OF CONCEPTIONS ABOUT DISEASES AND THERAPIES IN BYZANTIUM Byzantine doctors generally dealt with several issues of human health, following the patterns of the ancient Greek physicians and in particular Hippocrates, Dioskourides and Galen. One of the most important issues included in their texts is diet and its relation to health. As a result, a basic category of byzantine medical texts are nutritional manuals. The authors refer to nutritional value of foods, and the medicinal properties of each food, because they consider that there is a direct interaction between food and a proportion of the four fluids (χυμοί) of the human organism, according to ancient Greek medical concepts: blood, phlegm yellow bile and black bile. Disruption of the proportion of fluids (χυμοί) in the human organism is considered as primarily responsible for the appearance of malfunctions and disease. On the contrary, a balanced ratio of fluids is crucial for maintaining good health. Animal products are frequently mentioned in byzantine medical texts, either as dietary items, or as pharmaceutical preparations for the prevention and treatment of several diseases. In the present study suggested remedies of diseases with the use of animal products are mentioned analytically, as recorded in the texts of byzantine physicians. In an addendum diseases are described as they are recorded in the texts, aiming at a comparatively studying their appellation both in Byzantine and Modern medicine.